SIFAT PAPAN BLOK DARI LIMBAH EKSPLOITASI - Suwandi Kliwon; Paribotro Sutigno; M I Iskandar (Jurnal Penelitian Hasil Hutan, 1986)
A study on the physical and mechanical properties of block-board using core strip from 4 species of loging wastes has been undertaken and the results presented in this paper. The result shows that the everage value of block-board moisture content, density and strip density are 9.85%; 0.47 % and 0.43% respecttively. The bending strength of the block-board varies from 457.41 kg/cm2 (Jelutung) and 465.22 kg/cm2 (Perupuk) for paralel to the grain of the face and back veneer. The bending strength perpendicular to the grain of the outer veneer varies from 219. 76 kg/cm2 (Jelutung) and 418.85 kg/cm2 (Perupuk). The block-board samples which uses core strips from the 4 wood species have glue shear strength properties which complies with the Indonesian, German and Japanesse (JAS) standard, while the delamination complies only with Japanesse (JAS) standard.